A Tempo-Spatial Survey of Degree Day (Heating and Cooling) in Iran - Abolfazl Masoodian; Bohlol Alijani; Reza Ebrahimi (جغرافیا و پایداری محیط)
Being in different geographical latitudes, the existence of a variety of uneven lands, and the entrance of diverse synoptic systems during the year are among the major factors affecting Iran’s climate. One of the main parameters which determine the climate of a region is temperature in degree-day, which is the average daily air temperature. We intend to calculate, depict, and analyze both the average monthly, seasonal, and annual cooling degree-day and the average monthly, seasonal and annual heating degree-day of the country through temperature thresholds of 25 degrees using Asfazary database. This database includes average daily temperature from 1962 till 2003 on cells with dimensions of 15*15 kilometers across the country .Therefore, average daily temperature in Asfazary database is an array with dimensions of 15992*7187 whose lines show time (day) and the columns place (cells equal to15*15 kilometers). The average daily temperature in database Asfzary array has dimensions of 7187 * 15 992 whose rows indicate the time (day) and the columns location (cell). by adding the average cooling and heating degree days up monthly energy plans were obtained. Then by adding seasonal energy balance we got the required seasonal energy map, and finally by accumulating the average annual energies the required annual energy balance was achieved. Results of the analysis of monthly mean maps of the country’s energy balance represent a macro-climatic zoning in Iran. In the warm half of year, the flat part needs a higher energy balance due to higher cooling. But in the second half of year the uneven part is in need of the most energy balance.